ANOCOMPOSITE THERMOELECTRIC MATERIALS PRODUC- TION, PROPERTIES, USING (REVIEW) - Фреїк, Дмитро Михайлович; Криницький, Олександр Степанович; Матківський, Остап Миколайович (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY. Number, 2019)
Detailed analysis of the technological methods used to obtain nanocomposite structures of semiconductor thermoelectric materials and methods of compaction in solid samples. Particular attention is paid to the characteristics of different classes of compounds for nanocomposites: structure, thermal and electrical properties, compaction methods and ways of use. Highlighted new strategies in obtaining nanocomposites.